ESTABLISHING DIAGNOSTIC REFERENCE LEVELS FOR CARDIAC COMPUTED TOMOGRAPHY ANGIOGRAPHY IN SAUDI ARABIA. Issue 2 (17th January 2018) - Alhailiy, Ali B; Kench, Peter L; McEntee, Mark F; Brennan, Patrick C; Ryan, Elaine A
Abstract: Cardiac computed tomography angiography (CCTA) is a commonly used diagnostic imaging tool for cardiovascular disease. Despite constant improvements to imaging technologies, the radiation dose to patients remains a concern when using this procedure. Diagnostic reference levels (DRLs) are used as a trigger to identify and alert individual facilities that are using high doses during CT. This study aims to assess patient radiation dose and establish new national DRLs (NDRL) associated with CCTA in Saudi clinical practices. A structured booklet survey was designed for recording patient and scanning protocols during CCTA procedures. The data were collected retrospectively from the participating centres. NDRLs for CCTA were defined as the 75th and 25th of volumetric CT dose index (CTDIvol ) and dose length product (DLP). Specific DRLs based on two main ECG-gating modes were also proposed. Data sets related to 197 CCTAs with a mean weight of 77 kg were analysed in detail. The DRL values for CTDIvol and DLP for prospective gating mode and retrospective gating mode were 29 and 62 mGy and 393 and 1057 mGy cm, respectively. NDRLs for CCTA in Saudi Arabia are comparable or slightly lower than European DRLs due to the current use of dose-saving technology. There are major variations in patient doses during CCTA due to differences in CT scanners, scanning modes and departmental CCTA protocols.